Semaphorin-3A Promotes Degradation of Fragile X Mental Retardation Protein in Growth Cones via the Ubiquitin-Proteasome Pathway - Takabatake, Masaru; Goshima, Yoshio; Sasaki, Yukio (Frontiers in Neural Circuits, 2020)
Fragile X mental retardation protein (FMRP) is an RNA-binding protein that regulates local translation in dendrites and spines for synaptic plasticity. In axons, FMRP is implicated in axonal extension and axon guidance. We previously demonstrated the involvement of FMRP in growth cone collapse via a translation-dependent response to Semaphorin-3A (Sema3A), a repulsive axon guidance factor. In the case of attractive axon guidance factors, RNA-binding proteins such as zipcode binding protein 1 (ZBP1) accumulate towards the stimulated side of growth cones for local translation. However, it remains unclear how Sema3A effects FMRP localization in growth cones. Here, we show that levels of FMRP in growth cones of hippocampal neurons decreased after Sema3A stimulation. This decrease in FMRP was suppressed by the ubiquitin-activating enzyme E1 enzyme inhibitor PYR-41 and proteasome inhibitor MG132, suggesting that the ubiquitin-proteasome pathway is involved in Sema3A-induced FMRP degradation in growth cones. Moreover, the E1 enzyme or proteasome inhibitor suppressed Sema3A-induced increases in microtubule-associated protein 1B (MAP1B) in growth cones, suggesting that the ubiquitin-proteasome pathway promotes local translation of MAP1B, whose translation is mediated by FMRP. These inhibitors also blocked the Sema3A-induced growth cone collapse. Collectively, our results suggest that Sema3A promotes degradation of FMRP in growth cones through the ubiquitin-proteasome pathway, leading to growth cone collapse via local translation of MAP1B. These findings reveal a new mechanism of axon guidance regulation: degradation of the translational suppressor FMRP via the ubiquitin-proteasome pathway.